PEMBERATAN TERHADAP ANGGOTA TNI YANG MELAKUKAN PENGANIAYAAN MENGAKIBATKAN MATI - Prasetya, Muhammad Djaelani (UNES Law Review, 2023)
This research aims to analyze the aggravation of members of the TNI who commit torture resulting in death.This research uses normative legal research with a statutory approach (statute approach) and a case approach (statute approach) with the following steps: (1) identifying legal facts and eliminating irrelevant matters; (2) collecting legal and non-legal materials; (3) conducting a review of legal issues; (4) drawing conclusions and providing prescriptions.The results of the research show that first, reviewing Decision No. 61-K/PM I-04/AD/VII/2020 and Decision No. 161-/PM.II-08/AD/VIII/2020 based on a) case of position, has described criminal events, criminal acts, and criminal acts, and b) mitigating and aggravating circumstances, has described differences. Second, the weighting of TNI members who commit abuse resulting in death can be determined through 1) the defendant being a member of the TNI, 2) Article 52 of the Criminal Code, 3) Article 131 of the Military Criminal Code, and 4) causing death.